Small-Scale Tuna Fishers in Leihitu Sub-district: â€œan Ethnographic Study For its Developmentâ€ - Rumbouw, Burhanudin; Tupamahu, Agustinus; Tawari, Ruslan H.S. (Agrikan Jurnal Agribisnis Perikanan, 2024)
Leihitu waters are known as one of the areas with promising fisheries potential. However, the level of utilization of fisheries potential has not been managed evenly, even the level of welfare is still far from the expectations of the fishing community. This research will examine the extent to which the level of activity of utilization and management of fisheries resources in Leihitu as one of the fishermen's life support loci in terms of economic and cultural aspects based on ethnofisheries to improve Leihitu fisheries development and sustainable fisheries development strategies in Leihitu as an effort to increase productivity for local fishermen who carry out fishing business activities. This research was conducted for 6 months starting from October 2022-March 2023, In qualitative research, the researcher is the key instrument. Formulating a strategy for sustainable management of small-scale Madidihang tuna fishing resources based on ethnography was analyzed using SWOT analysis. Suitable strategies used, among others: conducting socialization and training to increase the capacity of fishermen, the importance of the role of historical, cultural, religious and artistic institutions and cooperation between communities and institutions. The strategy for sustainable management of Ethnography-based Small-Scale Madidihang Tuna fishermen resources in Leihitu District, namely conducting socialization and training, is to be able to produce not only limited to their own consumption and the production of fish.